Islamic Education Curriculum Based on Environmental Awareness at Madrasah Tsanawiyah Al Mansyuriyah Lombok Tengah Year 2024 - Sahrizal Fahlawi; Pertiwi, Rizka Eliza (Journal of Practice Learning and Educational Development, 2025)
Recently, environmental issues have become a significant concern for global leaders, prompting governments worldwide to take various measures to address these problems. In Indonesia, systematic efforts are underway, particularly through educational institutions, with Islamic education playing a key role by implementing environmentally-oriented curricula. This research was conducted at Al Mansyuriyah Junior Islamic School in Central Lombok. Data was gathered using several methods, with interviews being the primary technique, alongside observations. From the studies conducted, it can be concluded that environmental issues presented in the Akidah Akhlak (Faith and Morality) subjects, especially in the first semester of seventh grade, focus on personal hygiene discipline. This includes actions such as maintaining cleanliness, waste management, organizing clothing, and avoiding unhygienic behavior, with an emphasis on the negative impacts of indiscipline. In contrast, the second semester of sixth grade introduces environmental topics that shape morality towards living beings, including animals and plants. The curriculum covers ethical interactions with these beings and the potential negative consequences of immoral behavior towards them. However, it is important to note that environmental education within the Akidah Akhlak subjects has not yet fostered sufficient awareness about environmental concern. The themes taught still offer a limited understanding of the environment, focusing on competencies like cultivating virtuous morals, avoiding negative behavior, and reinforcing basic values such as discipline and cleanliness in daily life.